Seed production lines of maize: population density and interaction. - Virgen-Vargas, Juan; Zepeda-Bautista, Rosalba; Ávila-Perches, Miguel Ángel; Espinosa-Calderón, Alejandro; Arellano-Vázquez, José Luis; Gómez-Vázquez, Alfredo Josúe (Agronomía Mesoamericana, 2014)
The aim of this study was to determine the effect of population density and production site on the morphology, productivity and seed quality of parental lines of INIFAP maize hybrids from Valles Altos, Mexico. Evaluations were carried out from 2006 to 2008, in Coatlinchan, municipality of Texcoco, in the state of Mexico at 2250 masl). Sixteen parental lines comprising H-40, H-48, H-50, H-52, H-64E, H-66, H-68E, H-70, H-72E, H-74E, H-76E and H-78E were seeded at population densities of 62 500 and 82 500 plants per hectare in a randomized complete block design with three replicates. Significant differences (p≤0.05) were observed between different lines, population densities and year of harvest. In general lines had took 73 to 78 days for male flowering, and 82 to 83 days for female flowering. Lines yielded between 1484 and 7744 kg/ha, with large seed increases in the range of 14 to 86%, and volumetric weights between 57 to 70 and kg/hl. At a density of 82 500 plants/ha the seed yield increased 13% but the weight per thousand seeds decreased a 2.5% compared to that obtained at 62500 plants/ha. During this study the start of both the male and female flowering varied approximately three to four days. We also observed peaks on productivity in terms of yield and volumetric weight during 2008 (4427 kg/ha and 71.75 kg/hl, respectively), while in 2007 we observed the highest production of large seed (29.59 to 46.93%). The lowest yield was observed during 2006. We conclude that production of hybrid seed requires careful choice of lines, location and knowledge of the interaction between the genotype and the environment.